2009
DOI: 10.1128/aac.01485-08
|View full text |Cite
|
Sign up to set email alerts
|

An ABC Transporter of Streptococcus pneumoniae Involved in Susceptibility to Vancoresmycin and Bacitracin

Abstract: Vancoresmycin is a novel tetramic acid antibiotic, probably interfering with functions of the cytoplasmic membrane. To investigate its mode of action, mutants of Streptococcus pneumoniae exhibiting reduced susceptibility to vancoresmycin were isolated at a low frequency. Four of them were further examined and showed similar pleiotropic phenotypes, including reduced growth rate, early autolysis, and chain formation. In one mutant, the level of transcripts from a single locus encoding the potential ABC transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…This is the same TCS identified previously, albeit without experimental evidence, as the most likely regulator of spr0812-spr0813 expression (Fig. 6B) (5). Thus, the phylogenetic classification presented here provides a useful tool for the prediction of likely candidate systems for investigations into the regulatory mechanisms of such orphan transporters.…”
Section: Vol 193 2011 Evolution Of Antimicrobial Peptide Resistancementioning
confidence: 70%
See 1 more Smart Citation
“…This is the same TCS identified previously, albeit without experimental evidence, as the most likely regulator of spr0812-spr0813 expression (Fig. 6B) (5). Thus, the phylogenetic classification presented here provides a useful tool for the prediction of likely candidate systems for investigations into the regulatory mechanisms of such orphan transporters.…”
Section: Vol 193 2011 Evolution Of Antimicrobial Peptide Resistancementioning
confidence: 70%
“…Additionally, producer self-resistance against lantibiotics is often mediated by ATP-binding cassette (ABC) transporters, collectively termed LanFEG, consisting of two membrane-spanning subunits and one ATPase, which are encoded in the biosynthetic loci for the respective lantibiotic and whose expression is regulated by a two-component system (TCS) of the same genetic locus (21). Over the last decade, several ABC transporters of a different type have been identified as resistance determinants against peptide antibiotics in nonproducing strains (5,12,32,35,39,41,44,51). The permeases of these transporters share unique domain architecture with 10 transmembrane helices and a large extracellular domain (ECD) of about 200 amino acids between helices 7 and 8.…”
mentioning
confidence: 99%
“…Interestingly, a somewhat related ABC transporter in S. pneumoniae D39 (Sp0912-Sp0913; 52% and 26% identity to AnrA and -B, respectively) was recently found to contribute to the innate resistance of this strain to nisin, bacitracin, gramicidin (all are cell envelopeactive antimicrobials), and lincomycin (protein synthesis inhibitor). The other distant homologues of AnrB which have previously been linked to antimicrobial resistance include BceB, MbrB (both linked to bacitracin resistance [6,44]), YsaB, YvsC (both linked to nisin resistance [21,26]), and SPR0813 (linked to resistance to bacitracin and the novel tetrameric antibiotic vancoresmycin [4]). Notably, all of these homologues are members of the ABC M_9 subfamily (www-abcdb.biotoul .fr), whose members are thought to all be exporters due to the lack of associated substrate binding proteins (13).…”
Section: Discussionmentioning
confidence: 99%
“…The finding that SP0912-0913 is involved in resistance to antimicrobial compounds acting on the cell envelope, i.e., nisin and bacitracin, and antimicrobial compounds involved in protein synthesis inhibition, i.e., lincomycin (10), strongly suggests that the ABC transporter might be of the MDR type. Recently, Becker et al showed that this ABC transporter is indeed involved in resistance of S. pneumoniae R6 to bacitracin (3).…”
Section: Discussionmentioning
confidence: 99%